(3MGTjI Ydi GdeQGMs - (3CMeO eMeO GdTGaYj GdLfGLis; (3UGMH GdeQGM , CMeO Hf Ydj Hf eSYhO, MSGe GdOjf CHh GdaVGFd,J (B700 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdLfGLi gPg JbjjOGJ Ydi eJf GdeQGM LeYJ ef gGeT fSNI dhGdOi s
(3BNQgG (B:s
(3h ai bhdI Whi ETGQI Edi Gfg GdcJGH bO Je aJfHg dgPG s
(3eQGM GdCQhGM GfXQ cTa GdXfhf L(B2 (3U(B1651s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B175s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUQas